Immuntoleranzinduktion mit hoch dosiertem FVIII und intravenösen Immunglobulin-Pulsen - Stiefel, M.; Pinkwart, C.; Haase, R.; Merkel, N.; Forsberg, D.; Mauz-Körholz, C. (Hämostaseologie, 2010)
The development of neutralizing allo-antibodies against factor VIII (FVIII) or FVIII inhibitors is a severe complication in the treatment of haemophilia A. About 25% of the children with severe haemophilia A develop FVIII inhibitors. Here we report on a boy with severe haemophilia A and intron 22 inversion of the FVIII gene who was diagnosed at ten months of age. After 16 exposure days to FVIII (81 days after initial exposure) he developed a FVIII inhibitor (maximum: 9.76 BU/ml). Therapy: We started immune tolerance induction (ITI) according to the Bonn protocol with high dose plasma derived FVIII concentrate (100 IU per kg body weight) twice daily. For additional inhibitor elimination treatment the patient received intravenous immunoglobulin (ivIg) at a dose of 1–2 g/kg body weight every 4 to 6 weeks. After start of treatment a rapid decline of the inhibitor level was observed, nevertheless low FVIII inhibitor levels persisted (<5 BU/ ml). Furthermore, the FVIII half-life was still accelerated. However, after every course of ivIg the inhibitor level declined and FVIII half-life was prolonged. Currently, the FVIII half-life is approaching normal values after more than seven months of ITI duration. Conclusion: Additional application of immunoglobulin is beneficial for immune tolerance induction.
Keywords: Haemophilia A; FVIII inhibitors; ivIg